Desenvolvimento e avaliação de um método in vitro para estimar a degradabilidade das proteínas no rúmen - Härter, Carla Joice (2009)
A set of assays was carried out to develop a method for estimating ruminal degradation of proteins based on ammonia production in vitro. Samples of soybean meal, meat and bone meal, ryegrass (Lolium multiflorum) and cynodon (Cynodon dactilon var. Dactylon) were incubated by using the procedures of the in vitro/gas method. The effects of sample amount; starch inclusion to correct for ammonia uptaked by bacteria; nitrogen concentration in buffer solution and preview treatment of samples for soluble nitrogen extraction were evaluated. Short-time in vitro assays were also carried out to estimate degradation rate or solubilization rate of soluble fraction of nitrogen. Results of protein degradation obtained for some samples incubated in vitro were compared to those obtained from in situ and in vivo assays carried out in parallel. Results of protein degradation of different samples were not affected by sample size (15 mg N/ sample 1 g of sample) whereas degradability and dagradation rate of ryegrass protein, without starch correction, was negativelly affected by exclusion of ammonium bicarbonate from buffer solution (P<0,05). The preview extraction of soluble fraction of samples affected (P<0.05) protein degradation only of the ryegrass and soybean meal samples. Estimates of protein degradation for concentrate samples were not affected by starch inclusion. However, starch inclusion increased (P<0.05) protein degradation for ryegrass samples. Determination coefficient (r²) of regressions relating ammonia concentration and incubation time were usually high (above 0.80). Protein degradability of soybean meal, meat and bone meal and ryegrass samples were lower by in vitro than by in situ method (P<0.05). In turn, protein degradability of ryegrass and cynodon samples estimated in vitro was similar to obtained in vivo. In conclusion, although it needs more consistent validation, the in vitro/gas method might be an useful tool for estimating rumen degradabilty of proteins.